2005
DOI: 10.1093/jnci/dji432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Storage of Whole Plasma or Isolated Plasma DNA on the Results of Circulating DNA Quantification Assays

Abstract: Analysis of molecular markers in biological fluids has been proposed as a tool for early detection and monitoring of cancer. Circulating plasma DNA concentrations have been found to be higher in cancer patients than in cancer-free control subjects, but little is known about the effect of specimen storage on plasma DNA concentrations. Here we investigated the impact of long-term storage of both plasma samples and purified plasma DNA on the reproducibility of plasma DNA quantification as determined using real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 9 publications
2
89
2
4
Order By: Relevance
“…31 Our data indicate that while BRAFV600E can be detected in both serum and plasma from melanoma patients, plasma provides the best source to detect circulating BRAFV600E, although a direct comparison between serum and plasma was not obtained. In addition, our experiments indicate that DNA should be isolated from plasma samples and frozen in the setting of clinical monitoring studies, because its amount decreases after protracted storage, probably for degradation, and that the PCR techniques lose reproducibility, as recently shown by Sozzi et al 37 In contrast to that of patients, plasma and serum from healthy donors were reproducibly negative for the BRAFV600E marker. These results indicate that although the BRAFV600E mutation occurs at a high frequency also in benign melanocytic nevi, 28 it is not detectable in circulating DNA of healthy subjects with nevi.…”
Section: Discussionsupporting
confidence: 54%
“…31 Our data indicate that while BRAFV600E can be detected in both serum and plasma from melanoma patients, plasma provides the best source to detect circulating BRAFV600E, although a direct comparison between serum and plasma was not obtained. In addition, our experiments indicate that DNA should be isolated from plasma samples and frozen in the setting of clinical monitoring studies, because its amount decreases after protracted storage, probably for degradation, and that the PCR techniques lose reproducibility, as recently shown by Sozzi et al 37 In contrast to that of patients, plasma and serum from healthy donors were reproducibly negative for the BRAFV600E marker. These results indicate that although the BRAFV600E mutation occurs at a high frequency also in benign melanocytic nevi, 28 it is not detectable in circulating DNA of healthy subjects with nevi.…”
Section: Discussionsupporting
confidence: 54%
“…Third, concern has been raised with regard to the reliability of cfDNA mutation detection in stored blood samples (Sozzi et al, 2005;Daniotti et al, 2007). Previous reports have demonstrated that cfDNA mutations are no longer detectable in previously positive serum and DNA samples after 12 months of storage (Daniotti et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sample processing: within 6-8 h after collection (46)(47)(48) Use of specialized blood collecting tubes (Cell-Free RNA BCT 1 -Streck) that allow 7 days storage of blood by increasing cell stability and inhibiting nuclease mediated DNA degradation (48,49) 7-30% yearly DNA degradation during storage (50,51) cfDNA isolation:…”
Section: Kinetics Of Ddcfdna Levels In Recipients With Stable Graftsmentioning
confidence: 99%